Fearful symmetry in altered states: a bi-logic account of psychedelic action - Goldreich, Matthew (Frontiers in Psychology, 2025)
This conceptual study examines Matte Blanco’s system of bi-logic as a novel framework for understanding psychedelic altered states of consciousness. The initial point of departure is a consideration of the complex historical relationship between psychoanalysis and psychedelics, prompting a review of contemporary psychoanalytic and neuropsychoanalytic perspectives on psychedelic action. This leads into an exposition of bi-logic, which reformulates Freud’s conception of conscious and unconscious processes in terms of logico-mathematical principles, postulating binary modes of mental functioning: the asymmetrical mode of being, characterized by logic, differentiation, ordered relations in space and time, and cognition; and the symmetrical mode of being, characterized by symmetry, generalization, unity, spacelessness, timelessness, paradox, and boundless affect. The ‘bi-logic account’ elaborated here posits that psychedelic altered states tend towards the symmetrical mode of being: psychedelics shift the balance between these modes such that the symmetrical mode is increasingly prevalent in subjective experience and influential in mental functioning compared with ordinary states of consciousness. Having delineated this framing, its heuristic value in relation to the therapeutic use of psychedelics is discussed, particularly in the context of psychoanalytically-informed psychedelic therapy. Bi-logic is anticipated to contribute to a conceptual container which facilitates greater receptivity to, and integration of, experiences marked by intense affect, paradox, and the dissolution of self-other boundaries.